Kepemimpinan Transformasional dan Iklim Organisasi sebagai Determinan Prestasi Kerja Guru: Peran Mediasi Motivasi Berprestasi - Abdi Oriza; Ahmad Suriansyah; Metroyadi Metroyadi (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
This study aims to examine transformational leadership and organizational climate as determinants of teachers’ job performance, with achievement motivation positioned as a mediating variable. A quantitative explanatory design employing path analysis was used to test the proposed structural model. The sample consisted of 165 civil servant teachers from 26 public elementary schools in Central Banjarmasin District, selected through proportionate random sampling. Data were collected using a five-point Likert-scale questionnaire that met established validity and reliability criteria. The findings indicate that transformational leadership and organizational climate have positive and significant direct effects on teachers’ job performance. Transformational leadership also significantly influences achievement motivation, whereas organizational climate does not show a significant effect on achievement motivation. Mediation analysis reveals that achievement motivation partially mediates the relationship between transformational leadership and teachers’ job performance but does not mediate the relationship between organizational climate and job performance. The structural model explains 73.1% of the variance in teachers’ job performance. These findings highlight the importance of integrating transformational leadership practices with strategies that strengthen teachers’ achievement motivation as a key psychological mechanism for improving professional performance.